Managing expert knowledge in water network expansion project implementation. Issue 17 (2021) - de F. Anchieta, Thomaz F.; Santos, Saulo A.R.; Brentan, Bruno M.; Carpitella, Silvia; Izquierdo, Joaquín
Abstract: The implementation of expansion projects of water networks supplying growing cities is deemed to be a complex decision-making problem involving both technical aspects and expert knowledge. Management and control processes must rely on experts in the field whose know-how must be coupled with techniques able to deal with the natural subjectivity that affects input evaluations. Given the presence of many decision-making elements, the choice of proper hydraulic technical parameters may be linked to the main aspects of analysis requiring formal expert evaluation. In this contribution, the simulation of hydraulic indicators is integrated with a multi-criteria approach able to eventually determine those areas of a water network through which organising the expansion may be more beneficial. The software EPAnet 2.0 is first used for hydraulic simulations, whereas the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) will eventually rank network's nodes. A case study is solved to demonstrate the applicability and effectiveness of the proposed approach.